Effect of thermal treatment on the swelling and surface roughness of common alder and wych elm wood - Aytin, Ayhan; Korkut, Süleyman (Journal of forestry research, 2016)
Wood heat treatment has increased signifi- cantly in recent years and is still growing as an industrial process to improve some wood properties. We studied the change of swellingand surface roughness of common alder （Alnus glutinosa （L.） Gaertn. ssp.glutinosa） and wych elm （Ulmus glabra Huds.） woods after heat treatment at two different temperatures and durations. The temperatures were 180 and 200 ℃ and the durations were 2 and 4 h. A stylus method was employed to evaluate the surface char- acteristics of the samples. Roughness measurements by the stylus method were made in the direction perpendicular to the fiber on the wood surface. Four main roughness parameters, mean arithmetic deviation of profile （Ra）, mean peak-to-valley height （Rz）, root mean square roughness （Rq）, and maximum roughness （Ry） were used to evaluate the effect of heat treatment on the surface characteristics of the specimens. Swelling and surface roughness parameters （Ra, Rz, Ry, and Rq） differed significantly for two temper- atures and two durations of heat treatment. Swelling and surface roughness values decreased with increasing treat- ment temperature and treatment times.